2019
DOI: 10.1021/jacs.9b06749
|View full text |Cite
|
Sign up to set email alerts
|

Resorcinarene Cavitand Polymers for the Remediation of Halomethanes and 1,4-Dioxane

Abstract: Disinfection byproducts such as trihalomethanes are commonly found in drinking water. Trihalomethanes are formed upon chlorination of natural organic matter found in many drinking water sources. Inspired by molecular CHCl3⊂cavitand host–guest complexes, we designed porous polymers composed of resorcinarene receptors. These materials show higher affinity for halomethanes than a specialty activated carbon used for trihalomethane removal. The cavitand polymers show similar removal kinetics as activated carbon and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Reproducedfrom Ref. [37] with permission from the AmericanC hemical Society,c opyright 2019. Figure 12.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproducedfrom Ref. [37] with permission from the AmericanC hemical Society,c opyright 2019. Figure 12.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dichtel et al integrated resorcinarene into porous polymer networks and showed that the resulting materials were able to remove trihalomethane from water ( Figure 11). [37] Thep reparation of these materials relied on nucleophilic aromatic substitution of tetrafluoroisonicotinonitrile (TFIN) or TFN (2)w ith resorcinarene to give the cavitand-containing polymers CP-TFIN and CP-TFN,r espectively.T he polymers prepared using the TFIN linker consistently demonstrated ah igher removal percentage for all the MPs tested. For instance, CP-TFIN was found to remove over 85 %o ft he CHCl 3 from an aqueous source phase leaving ar esidual CHCl 3 concentration below 15 mgL À1 .…”
Section: Resorcinarene-containing Covalent Polymer Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Thec ross-linked polymers containing amide naphthotubes have been characterized by various analytical methods. In the solid-state cross-polarization magic angle spinning (CP/ MAS) 13 CNMR spectra of P1 and P2 (Figure 2a), no alkyne peaks (at ca. 80 ppm for 2a and 2b)were detected, suggesting that the alkyne groups were converted and the cross-linked polymers are formed.…”
Section: Guestsmentioning
confidence: 99%
“…This is because macrocycle‐based host–guest interactions are often sensitive to changes in the environmental conditions, including pH, light, temperature, pressure, redox conditions, anions, cations, solvent, and so on [9–13] . Common macrocycles that have been incorporated into polymeric networks for water purification include cyclodextrins (CDs), [14–20] calixarenes, [21–26] pillararenes, [27–32] resorcinarenes, [33–37] and imidazolium macrocycles [38–41] . On the other hand, other typical macrocycles, including crown ethers, [42–44] cucurbiturils (CBs), [45–47] and calix[4]pyrroles (C4Ps,) [48–50] have not yet been widely used in this context.…”
Section: Introductionmentioning
confidence: 99%